GREEN VOLUNTEER-BASED GRID SCHEDULING - ISMAIL, NORZATUL NATRAH (2015)
Heavy job processing load increases the temperature of a computer. High temperature leads to machine failure and affects the computational performance of the machine. It is essential to reduce the temperature of the computers that is processing a heavy load in order to get the best performance. Recent advancement in high performance computing research in Universiti Teknologi PETRONAS has seen the deployment of UTP campus grid. The main part of the campus grid is a volunteerbased grid cluster, distributed in undergraduate labs. During office hours and weekdays, the air-conditioning in the labs is turned on. At this period of time, the airconditioning reduces the temperature of the machines. It is imperative to allow these machines to work at their best performance even during out of office hours when the air-conditioning is off. This is because during out-of-office hours, the heavy processing is less likely to be interrupted by the routine office jobs.